Identification of the late Quaternary activity of the littoral fault zone at the Northern Jiangsu province in China - Ji, Haomin; Ren, Zhikun; Zhu, Menghao; Min, Wei; Liu, Jinrui; Feng, Yingci (Frontiers in Earth Science, 2023)
It has been accepted the existence of the Littoral Fault Zone at northern Jiangsu Province (LFZ), but its geometric distribution and the late Quaternary activity are still controversial. In this study, to constrain its late Quaternary activity, we collected two high-resolution shallow reflection seismic profiles crossing the northern segment of the Littoral Fault Zone (NLFZ) in the Yellow Sea, using mini-multichannel seismograph. Four reflection interfaces were identified clearly in reflection profiles, dividing Quaternary strata in the study area into four seismic units. Combined with the existing regional borehole data, it is inferred that these units correspond to strata in the Holocene, the Late Pleistocene, the Middle Pleistocene and the Early Pleistocene, respectively. The breakpoints F1, F2, F3, F4, F5, and F6 correspond to NLFZ and uppermost offset marker is the Late Pleistocene-Holocene interface. Therefore, NLFZ is tentatively identified as a Late Pleistocene-Holocene active fault. Our method utilized to obtain high resolution profiles also provides a good example for researches at similar sites. Moreover, considering the regional tectonic background, its fault length and long aseismic period, NLFZ is capable of generating strong earthquakes of Mw 6.5 or above in the future, which needs further investigation. Finally, based on our profiles and previous studies, it is inferred that the kinematic properties of LFZ transformed at the Middle Pleistocene at least.